Overcoming challenges in mainstream Anammox applications: Utilization of nanoscale zero valent iron (nZVI) - KOCAMEMİ, BİLGE; ERKEN, ESRA; YÜCESOY ÖZKAN, ZEYNEP (ELSEVIER, 2019)
Although Anammox process is a proven technology for sidestream nitrogen removal, the process faces challenges for mainstream applications in sewage treatment plants (STPs). The aim of this study was to investigate the effect of zero valent iron nanoparticles (nZVI) on process performance to eliminate confronts for mainstream applications. An SBR (sequencing batch reactor) system was fed with various nZVI concentrations (0.04-5000 ppb) within 310 days of operation. Ammonium (NH4+N) and nitrite (NO2-N) removal rates showed 58% increase in daily measurements and 73% increase in instant measurements. Specific Anammox Activity (SAA) was noticeably higher on the days the system was exposed to nZVI compared to the unexposed days. EPS secretion, which enhances granulation of Anammox bacteria was favored by nZVI. Despite lower sludge retention time (SRT) values, the fraction of Anammox bacteria in total bacteria reached to 91-92% implying a boosting effect of nZVI on growth rate of Anammox bacteria. High Resolution Melting (HRM) analyses showed that four distinct clades were present in the reactor. (C) 2018 Elsevier By. All rights reserved.
Keywords: Nanoparticles; Mainstream nitrogen removal; Wastewater; ANAEROBIC AMMONIUM OXIDATION; NITROGEN REMOVAL; GRANULAR SLUDGE; START-UP; REACTOR; PERFORMANCE; BACTERIA